Enzymatic aminoacylation of an eight-base-pair microhelix with histidine. - Francklyn, C (1990)
The major determinant for the identity of alanine tRNAs is a single base pair in the acceptor helix that is proximal to the site of amino acid attachment. A 7-base-pair microhelix that recreates the acceptor helix can be charged with alanine. No other examples of charging of small helices with specific amino acids have been reported, to our knowledge. We show here that a 13-base-pair and an 8-base-pair hairpin helix that reconstruct a domain and subdomain, respectively, of histidine tRNAs can be charged with histidine. We also show that transplantation of a base pair that is unique to histidine tRNAs is sufficient to consider histidine acceptance on a domain and subdomain of alanine tRNA. Both alanine and histidine aminoacyl-tRNA synthetases retain specificity for their cognate synthetic substrates. Alanine- and histidine-specific microhelices may resemble a system that arose early in the evolution of charging and coding.